A Rare Presentation of Type 2 Lepra Reaction: Necrotizing Erythema Nodosum Leprosum with Extensive Ulceration - Ariani, Tutty; Clarissa Maharani Putri (HM Publisher, 2025)
Background: Leprosy, primarily caused by Mycobacterium leprae, is a chronic infectious disease that mainly affects the skin and peripheral nerves. Type 2 leprosy reaction (ENL) is an immune complex-mediated complication characterized by inflammation of the skin, nerves, and other organs. A less common manifestation of ENL is necrotizing ENL, which presents with extensive skin necrosis and ulceration. This case report describes a rare presentation of necrotizing ENL with extensive ulceration in a young woman with borderline lepromatous leprosy. Case presentation: A 20-year-old female presented with multiple, progressively enlarging, painless ulcers on her right leg and painful reddish nodules on her left arm and left leg. She had a history of borderline lepromatous leprosy. Dermatological examination revealed madarosis, infiltration, nodules, hyperpigmentation macules, ulcers, and blackish crusts. Sensory testing showed hypoesthesia in the abdomen and back, and anesthesia in both lower arms and legs. Histopathological examination confirmed the diagnosis of necrotizing ENL. Conclusion: Necrotizing ENL is a rare and severe complication of leprosy. This case highlights the importance of early diagnosis and appropriate management with multi-drug therapy and corticosteroids to prevent significant morbidity and disability.